(untitled) (Ustozlar uchun, 2024)
Abstract: In this article, the problems encountered in attracting foreign direct investments to our country, reforms and solutions are analyzed. The latter through econometric time series analysis.Investments of the past 30 years were studied and analyzed, and predictions for the next years were given.